Karakter Ideal Konselor Multibudaya Berdasarkan Nilai Luhur Semar - Setyaputri, Nora Yuniar (Jurnal Kajian Bimbingan dan Konseling, 2017)
Nowadays a lot of counselor labeling their counselee which caused counselor’s lack of multicultural insights. Labeling may have a poor impact on the counselor’s decision in selecting counseling intervention strategies. The multicultural insights of counselors must be enhanced by building an ideal character in themselves. This ideal character is concerned with the understanding and behavior of counselors to respond the condition of heterogeneous counselees and how high the curiosity, interest and motivation of counselors to constantly add multicultural insights that they have. The noble values contained within Semar can be attributed to how the ideal character of multicultural counselors. This study aims to explain the ideal character of multicultural counselor taken from the noble value of Semar as well as linking the character with multicultural competence of counselor. This research uses qualitative approach of library research type. The ideal characteristics of multicultural counselors that can be formulated include: (1) religious; (2) neutral; (3) tolerance; (4) sincere; (5) discipline; (6) social care; (7) friendly; (8) fair; (9) honest; (10) supple; (11) democratic; and (12) curiosity.